2020
DOI: 10.3390/d12100383
|View full text |Cite
|
Sign up to set email alerts
|

Diatom Diversity on the Skin of Frozen Historic Loggerhead Sea Turtle Specimens

Abstract: In recent years, biofilm-forming diatoms have received increased attention as sea turtle epibionts. However, most of the research has focused on carapace-associated taxa and communities, while less is known about diatoms growing on sea turtle skin. The current study investigated diatom diversity on the skin of loggerhead sea turtle heads detached from the carcasses found along the Adriatic coast between 1995 and 2004 and stored frozen for a prolonged period of time. By using both light and scanning electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The epimicrobiomes of sea turtles, in turn, have received far less attention. Recent years brought increased interest in 10.3389/fevo.2022.907368 micro-eukaryotic surface assemblages of sea turtles largely due to a series of projects exploring the diversity of sea turtleassociated diatoms (Majewska et al, 2015;Robinson et al, 2016;Rivera et al, 2018;Azari et al, 2020;Kanjer et al, 2020;Van de Vijver et al, 2020). Those studies identified a group of the diatom core taxa typical of sea turtles but also showed some biogeographic differences between diatom epizoic assemblages ( Van de Vijver et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The epimicrobiomes of sea turtles, in turn, have received far less attention. Recent years brought increased interest in 10.3389/fevo.2022.907368 micro-eukaryotic surface assemblages of sea turtles largely due to a series of projects exploring the diversity of sea turtleassociated diatoms (Majewska et al, 2015;Robinson et al, 2016;Rivera et al, 2018;Azari et al, 2020;Kanjer et al, 2020;Van de Vijver et al, 2020). Those studies identified a group of the diatom core taxa typical of sea turtles but also showed some biogeographic differences between diatom epizoic assemblages ( Van de Vijver et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The epimicrobiomes of sea turtles, in turn, have received far less attention. Recent years brought increased interest in micro-eukaryotic surface assemblages of sea turtles largely due to a series of projects exploring the diversity of sea turtle-associated diatoms (Majewska et al, 2015; Robinson et al, 2016; Rivera et al, 2018; Azari et al, 2020; Kanjer et al, 2020; Van de Vijver et al, 2020). Those studies identified a group of the diatom core taxa typical of sea turtles but also showed some biogeographic differences between diatom epizoic assemblages (Van de Vijver et al, 2020).…”
Section: Introductionmentioning
confidence: 99%